THE ROLE OF ECONOMIC DEVELOPMENT O IN ECONOMIC GROWTH FROM 2004 TO 2021 IN IRAQ - Humoud Saad Muhaimid; Monketh Ibrahim Saleh Hamad (Scholars Digest Publishing, 2025)
One of the various assets of renewed intercourse with other states worldwide could become increased financial capabilities of both foreign and national organizations for investing in Iraqi infrastructure projects and business development. Along this line, the surge in investment in the eco-tourism sector not only results in an augmentation of the volume of GDP but also employs the citizens in the effortless creation of sophisticated living standards. Even though Iraq's security system is not stable and conflictual, as expressed in the many wars, conflicts, and acts of terrorism that have shaken the country, this fact makes it difficult for the country to strengthen its economy by attracting development projects and investing. The oil industry, with an essential role to Iraq economy, has been going through changes because of change in the world economy. Since 2003, following the defeat of the previous government, oil production has a notable significant increase, making economic development a priority to the country. However, such obstacles as shaky oil prices or unfavorable economic situation caused by the crisis of 2008 are transnational factors which might restrain economic development of Iraq. In addition to these external influences, concerns regarding security, corruption, and insufficient investment in sectors beyond oil have the potential to impede Iraq's economic growth. The objective of this study is to undertake a comprehensive analytical examination of the contribution of development to the promotion of economic growth in Iraq from 2004 to 2021. The research findings affirm that economic development has a positive effect on economic growth and makes a substantial contribution.
Keywords: Economic development, foreign trade, economic growth, Iraq.